Intranasal Flunisolide Suppresses Pathological Alterations Caused by Silica Particles in the Lungs of Mice - Ferreira, Tatiana Paula Teixeira; Lima, Januário Gomes Mourão e; Farias-Filho, Francisco Alves; Jannini de Sá, Yago Amigo Pinho; de Arantes, Ana Carolina Santos; Guimarães, Fernanda Verdini; Carvalho, Vinicius de Frias; Hogaboam, Cory; Wallace, John; Martins, Marco Aurélio; Silva, Patrícia Machado Rodrigues e (Frontiers in Endocrinology, 2020)
Silicosis is an occupational disease triggered by the inhalation of fine particles of crystalline silica and characterized by inflammation and scarring in the form of nodular lesions in the lungs. In spite of the therapeutic arsenal currently available, there is no specific treatment for the disease. Flunisolide is a potent corticosteroid shown to be effective for controlling chronic lung inflammatory diseases. In this study, the effect of flunisolide on silica-induced lung pathological changes in mice was investigated. Swiss-Webster mice were injected intranasally with silica particles and further treated with flunisolide from day 21 to 27 post-silica challenge. Lung function was assessed by whole body invasive plethysmography. Granuloma formation was evaluated morphometrically, collagen deposition by Picrus sirius staining and quantitated by Sircol. Chemokines and cytokines were evaluated using enzyme-linked immunosorbent assay. The sensitivity of lung fibroblasts was also examined in in vitro assays. Silica challenge led to increased leukocyte numbers (mononuclear cells and neutrophils) as well as production of the chemokine KC/CXCL-1 and the cytokines TNF-α and TGF-β in the bronchoalveolar lavage. These alterations paralleled to progressive granuloma formation, collagen deposition and impairment of lung function. Therapeutic administration of intranasal flunisolide inhibited granuloma and fibrotic responses, noted 28 days after silica challenge. The upregulation of MIP-1α/CCL-3 and MIP-2/CXCL-2 and the cytokines TNF-α and TGF-β, as well as deposition of collagen and airway hyper-reactivity to methacholine were shown to be clearly sensitive to flunisolide, as compared to silica-challenge untreated mice. Additionally, flunisolide effectively suppressed the responses of proliferation and MCP-1/CCL-2 production from IL-13 stimulated lung fibroblasts from silica- or saline-challenged mice. In conclusion, we report that intranasal treatment with the corticosteroid flunisolide showed protective properties on pathological features triggered by silica particles in mice, suggesting that the compound may constitute a promising strategy for the treatment of silicosis.